Perbedaan Pengaruh Edukasi antara Film dan Ceramah Terhadap Pengetahuan dan Sikap Deteksi Dini Kanker Serviks Ibu-Ibu di Dusun Krodan Sleman - Ratnaningrum, Paulina (Jurnal Farmasi (Journal of Pharmacy), 2013)
Cervical cancer is a malignant tumor that grows in the cervix are caused by Human Papillomavirus (HPV). Cervical cancer is the number one killer for women. According to data obtained from the Indonesian Cancer Foundation (2007) each year about 500.000 women diagnosed with cervical cancer and more than 250.000 died. Cervical cancer prevention can be done with papsmear. Papsmear can reduce cervical cancer mortality up to 50-60%. This research had pupose to know the difference influence education between movie and lecture to the knowledge and attitude on early detection of cervical cancer. This study was a quasi-experimental research with the design of pre-posttest intervention study with control group. The data was collected by using questionnaires and analyzed by using computer programs. The statistic analysis with Independent Sampels T-test showed significantly different increased of knowledge and attitude betwen movie and lecture on early detection of cervical cancer (p=0,002). Lecture was more effective than movie.